Multilayer explosion-proof nano film and manufacturing method thereof

By using a multi -layered nano -material material in the explosion -proof membrane, the problem of not much improvement of existing explosion -proof membrane explosion -proof performance is solved, and higher external anti -force performance and safety are achieved.

CN119371904APending Publication Date: 2025-01-28NANTONG TONGYI AEROSPACE SCI & TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411692233.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In the prior art, the explosion-proof film has not improved much in its explosion-proof performance, especially for the explosion-proof film of tempered glass, which is difficult to effectively enhance the glass's resistance to external force and prevent the risk of self-destruction.

Method used

The production method of multi -layer explosion -proof nanofillers is mixed with PET with carbon nanotubes, bulletproof glass fibers, nano ceramic particles and ultraviolet absorbers, and form a multi -layer structure through squeezing, traction and molding, including pressure sensitivity, including pressure sensitivity. The glue layer, polymerization layer, scratch -resistant coating and composite glue layer enhance the explosion -proof and thermal insulation performance of the membrane.

Benefits of technology

While maintaining a conventional explosion -proof membrane anti -ultraviolet and insulation function, it has good explosion -proof and thorns, which significantly improves the external force performance and safety of glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371904A_ABST
    Figure CN119371904A_ABST
Patent Text Reader

Abstract

The invention discloses a multilayer explosion-proof nano film and a manufacturing method thereof, and relates to the technical field of material science. The invention relates to a manufacturing method of a multilayer explosion-proof nano film, which comprises the following steps: (1) respectively blending PET (Polyethylene Terephthalate) with a carbon nano tube and bulletproof glass fiber to prepare a PET base material 1; (2) blending PET with nano ceramic particles and an ultraviolet absorbent respectively to prepare a PET base material 2; (3) coating the surface of the PET base material 1 with a pressure-sensitive adhesive coating solution to prepare a semi-finished product 1; (4) coating the surface of the semi-finished product 1 with a polyurea coating solution to prepare a semi-finished product 2; (5) coating the surface of the PET base material 2 with a scratch-resistant coating solution to prepare a semi-finished product 3; and (6) coating the surface of the semi-finished product 3 with a composite adhesive coating liquid, and laminating the semi-finished product 3 with the semi-finished product 2 of which the protective film is torn off to prepare the multi-layer anti-explosion nano-film. The explosion-proof membrane prepared by the invention has heat insulation and ultraviolet resistance of a conventional explosion-proof membrane, also has explosion-proof and puncture-proof functions, and is good in safety performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material science, and in particular to a multi-layer explosion-proof nano film and a manufacturing method thereof. Background Art

[0002] Glass is widely used in daily life, and is used in homes, buildings, cars, high-speed trains, airplanes, instruments, etc. However, whether it is ordinary glass, tempered glass, or special glass, when the destructive force reaches a certain level, it will break, and many types of glass also have the risk of "self-explosion". In order to enhance the glass's resistance to external forces and avoid self-explosion, the usual method is to stick a layer of film on the surface of the glass. On the one hand, it enhances the glass's resistance to external forces, and on the other hand, it can adhere to glass fragments to avoid causing harm to people. However, the current explosion-proof films on the market, especially those for tempered glass, mostly focus on the performance of heat insulation, UV protection, anti-glare and other effects, but have not greatly improved the explosion-proof performance.

[0003] Therefore, the present invention proposes a multi-layer explosion-proof nanofilm and a method for making the same to solve the problem that the explosion-proof performance is not greatly improved in the prior art. Summary of the invention

[0004] The purpose of the present invention is to provide a multi-layer explosion-proof nano film and a manufacturing method thereof to solve the problems raised in the prior art.

[0005] To achieve the above object, the present invention provides the following technical solution: a method for preparing a multi-layer explosion-proof nanofilm, comprising the following steps:

[0006] Step (1): PET is blended with carbon nanotubes and bulletproof glass fibers respectively, and the mixture is placed in a three-layer extruder for extrusion, pulling, and molding to form a three-layer structure of PET containing bulletproof glass fibers-PET containing carbon nanotubes-PET containing bulletproof glass fibers, thereby obtaining a PET substrate 1;

[0007] Step (2): PET is blended with nano-ceramic particles and ultraviolet absorber respectively, and the mixture is placed in a three-layer extruder for extrusion, pulling, and molding to form a double-layer structure of PET containing ultraviolet absorber and PET containing nano-ceramic particles, thereby obtaining a PET substrate 2;

[0008] Step (3): coating one side of the PET substrate 1 with a pressure-sensitive adhesive coating liquid, drying, and laminating with a base paper release film to form a three-layer structure of PET substrate 1-pressure-sensitive adhesive layer-base paper release film, thereby obtaining a semi-finished product 1;

[0009] Step (4): coating the other side of the PET substrate 1 with a polyurea coating liquid, drying, and laminating with a protective film to form a five-layer structure of protective film-polyurea layer-PET substrate 1-pressure-sensitive adhesive layer-base paper release film to obtain a semi-finished product 2;

[0010] Step (5): coating a scratch-resistant coating liquid on one side of the PET substrate 2 containing a UV absorber, drying, and laminating with a protective film to form a three-layer structure of protective film-scratch-resistant coating-PET substrate 2, thereby obtaining a semi-finished product 3;

[0011] Step (6): Coat the composite adhesive coating liquid on one side of the semi-finished product 3 containing nano-ceramic particles, dry it, and laminate it with the semi-finished product 2 with the protective film removed to form an eight-layer structure of protective film-scratch-resistant coating-PET substrate 2-composite adhesive layer-polyurea layer-PET substrate 1-pressure-sensitive adhesive layer-base paper release film to obtain a multi-layer explosion-proof nanofilm.

[0012] Furthermore, in step (1), the mass ratio of carbon nanotubes to PET is (1-10): 1000;

[0013] The mass ratio of bulletproof glass fiber to PET is (1-10):1000.

[0014] Further, the melting temperature in step (1) is 200-220°C;

[0015] The cooling temperature is 10-20℃.

[0016] Furthermore, in step (1), the thickness of the PET substrate 1 is 120-200 μm.

[0017] Further, carbon nanotubes: CAS number 308068-56-6, purity 99%, sourced from Shandong Tanfeng New Materials Technology Co., Ltd.;

[0018] PET: Brand FR530NC010, from Ningbo Oushuo New Materials Co., Ltd.

[0019] Bulletproof glass fiber: brand name EXL4419, sourced from Dongguan Juona New Materials Co., Ltd.

[0020] Furthermore, in step (2), the mass ratio of nano-ceramic particles to PET is (1-5): 1000;

[0021] The mass ratio of ultraviolet absorber to PET is (1-5):1000.

[0022] Further, the melting temperature in step (2) is 200-220°C;

[0023] The cooling temperature is 10-20℃.

[0024] Furthermore, in step (2), the thickness of the PET substrate 2 is 120-200 μm.

[0025] Further, the nano-ceramic particles are zirconium oxide nanoparticles, CAS number 1314-23-4, purity 99%, particle size 5 μm, sourced from Merck Life Sciences;

[0026] The ultraviolet absorber is UV-531 with a purity of 99%, which is sourced from Jinan Xiangfeng Weiye Chemical Co., Ltd.

[0027] Furthermore, in step (3), the thickness of the pressure-sensitive adhesive coating is 28-30 μm.

[0028] Furthermore, the drying process conditions in step (3) are: temperature 80-120° C., time 5-10 min.

[0029] Furthermore, the base paper release film in step (3) is a PET silicone oil release film with a thickness of 40-60 μm, which is sourced from Jiangsu Pingyu New Materials Co., Ltd.

[0030] Furthermore, the pressure-sensitive adhesive coating liquid in step (3) is prepared by the following process:

[0031] The polyacrylate, ethyl acetate, defoamer and leveling agent are mixed and stirred for 3-5 minutes, and dispersed at high speed to obtain a mixed solution 1. The p-phenylene diisocyanate and ethyl acetate are mixed and stirred for 3-5 minutes, and the mixed solution 1 is added and stirred for 10-15 minutes to obtain a pressure-sensitive adhesive coating liquid.

[0032] Furthermore, the mass ratio of polyacrylate, ethyl acetate, defoamer and leveling agent is (30-40): (50-60): (0.1-0.3): (0.1-0.3); the mass ratio of p-phenylene diisocyanate and ethyl acetate is (3-5): (5-7).

[0033] Furthermore, the process conditions for high-speed dispersion are: temperature 20-30°C, speed 2000-5000r / min, time 5-30min 。

[0034] Further, polyacrylate: CAS number is 9003-01-4, purity is 99%, and it is sourced from Jinan Huijinchuan Trading Co., Ltd.;

[0035] Ethyl acetate: CAS number is 141-78-6, purity is 99%, from Foshan Changxing New Materials Co., Ltd.

[0036] The defoamer was BASF FoamStar SI 2299, 99% pure, sourced from DKSH Chemical International Trading (Shanghai) Co., Ltd.;

[0037] The leveling agent is GS-1873, with a viscosity of 150-400cst, from Shanghai Zicheng International Trade Co., Ltd.

[0038] p-Phenylene diisocyanate: CAS number is 104-49-4, purity is 98%, derived from McLean reagent.

[0039] Furthermore, in step (4), the thickness of the polyurea coating is 5-10 μm.

[0040] Furthermore, the drying process conditions in step (4) are: temperature 80-120° C., time 5-10 min.

[0041] Furthermore, the protective film is a PET protective film with a thickness of 40-55 μm, which is sourced from Wuxi Boli Protective Film Co., Ltd.

[0042] Furthermore, the polyurea layer coating liquid in step (4) is prepared by the following process:

[0043] Ethyl acetate, toluene, butanone, diphenylmethane diisocyanate, polycaprolactone polyol and polytetramethylene ether diparaaminobenzoate are mixed and stirred, diethyltoluenediamine and dichlorodiphenylmethanediamine are added, stirring is continued, carbon nanotubes are added, and ultrasonic dispersion is performed to obtain a polyurea layer coating liquid.

[0044] Furthermore, the mass ratio of ethyl acetate, toluene, butanone, diphenylmethane diisocyanate, polycaprolactone polyol, polytetramethylene ether diparaaminobenzoate, diethyltoluenediamine, dichlorodiphenylmethanediamine, and carbon nanotubes is (50-60): (5-10): (5-10): (5-8): (10-20): (10-20): (3-5): (3-5): (1-5).

[0045] Furthermore, the stirring process conditions are: temperature 20-30°C, rotation speed 500-600r / min, and time 10-15min.

[0046] Furthermore, the process conditions of ultrasonic dispersion are: frequency 20-28 kHz, time 5-10 min.

[0047] Further, toluene: CAS number is 108-88-3, which is derived from Merck reagent;

[0048] Butanone: CAS number is 78-93-3, purity is 99.8%, sourced from Guangdong Xiaoda Chemical Co., Ltd.;

[0049] Diphenylmethane diisocyanate: CAS number is 101-68-8, from Merck reagents;

[0050] Polycaprolactone polyol: CAS number is 69089-45-8, from Hubei Watson Chemical Technology Co., Ltd.;

[0051] Polytetramethylene ether glycol p-aminobenzoate: CAS number is 54667-43-5, purity is 99%, from Wuhan Kanos Technology Co., Ltd.

[0052] Diethyltoluenediamine: CAS number is 68479-98-1, purity is 99.5%, sourced from Jinan Shengda Chemical Co., Ltd.

[0053] Dichlorodiphenylmethanediamine: CAS number is 101-14-4, purity is 99%, and it comes from Jiangsu Bost Chemical Technology Co., Ltd.

[0054] Furthermore, in step (5), the thickness of the scratch-resistant coating is 7-9 μm.

[0055] Furthermore, the drying process conditions in step (5) are: temperature 80-120° C., time 5-10 min.

[0056] Furthermore, the scratch-resistant coating liquid in step (5) is prepared by the following process:

[0057] The water-based acrylic resin, deionized water, defoamer, leveling agent and photoinitiator are mixed, stirred for 0.3-0.5h, and then the water-based acrylic resin and thickener are added again, and the mixture is stirred to adjust the viscosity to 900-1100 CPS to obtain a scratch-resistant coating liquid.

[0058] Furthermore, the mass ratio of the water-based acrylic resin, deionized water, defoamer, leveling agent, photoinitiator, the water-based acrylic resin added again, and the thickener is (30-35): (10-15): (0.1-0.5): (0.1-0.5): (1-5): (60-70): (0.5-1).

[0059] Further, water-based acrylic resin: CAS number is 9003-01-4, viscosity is 100-3000 cP, and is sourced from Guangzhou Haoyi New Materials Technology Co., Ltd.;

[0060] The photoinitiator is ethyl p-N,N-dimethylaminobenzoate, CAS No. 10287-53-3, purity 99%, from Jiangsu Rayne Environmental Protection Technology Co., Ltd.;

[0061] The thickener is sodium polyacrylate, CAS number 9003-04-7, purity 99%, sourced from Henan Mingzhixin Chemical Products Co., Ltd.

[0062] Furthermore, in step (6), the thickness of the composite adhesive coating is 10-30 μm.

[0063] Furthermore, the drying process conditions in step (6) are: temperature 80-120° C., time 5-10 min.

[0064] Furthermore, the composite adhesive coating liquid in step (6) is prepared by the following process:

[0065] Mix toluene, polyether diol, 1,3-propylene glycol, defoamer, leveling agent, blue dye, red dye and black dye, stir, add p-phenylene diisocyanate, continue stirring for 5-10 minutes, and obtain a composite adhesive coating liquid.

[0066] Furthermore, the mass ratio of toluene, polyether diol, 1,3-propylene glycol, defoamer, leveling agent, blue dye, red dye, black dye and p-phenylene diisocyanate is (35-40):(10-15):(1-5):(0.1-0.5):(0.1-0.5):(1-1.5):(1.5-2.0):(2.5-3):(40-50).

[0067] Furthermore, the stirring process conditions are: temperature 20-30°C, rotation speed 300-500r / min, and time 10-20min.

[0068] Further, polyether diol: hydroxyl value 510-623 mgKOH / g, purity 99%, sourced from Haian Petrochemical Plant, Jiangsu Province;

[0069] 1,3-Propanediol: CAS number is 504-63-2, purity is 99%, from Nanjing Oriental Pearl Industry and Trade Co., Ltd.;

[0070] The blue dye is acid blue 9, CAS number 3486-30-4, pH value 8.5-9.5;

[0071] The red dye is solvent red 135, CAS number 20749-68-2, purity 99%;

[0072] The black dye is solvent black 29, CAS number is 61901-87-9, purity is 99%, and all of them are from Anhui Jingzhicai New Materials Co., Ltd. BRIEF DESCRIPTION OF THE DRAWINGS

[0073] Figure 1 This is a schematic diagram of the structure of the PET substrate 1 obtained in Example 5 of the present invention.

[0074] Figure 2 Schematic diagram of the structure of the PET substrate 2 obtained in Example 5 of the present invention.

[0075] Figure 3 This is a schematic structural diagram of the semi-finished product 1 obtained in Example 5 of the present invention.

[0076] Figure 4 This is a schematic structural diagram of the semi-finished product 2 obtained in Example 5 of the present invention.

[0077] Figure 5 This is a schematic structural diagram of the semi-finished product 3 obtained in Example 5 of the present invention.

[0078] Figure 6 Schematic diagram of the structure of the multilayer explosion-proof nanofilm obtained in Example 5 of the present invention.

[0079] Figure 7 Schematic diagram of the bonding of the semi-finished product 2 and the semi-finished product 3 obtained in Example 5 of the present invention.

[0080] In the figure, 1-PET containing bulletproof glass fiber, 2-PET containing carbon nanotubes, 3-PET containing UV absorber, 4-PET containing nano-ceramic particles, 5-PET substrate 1, 6-pressure-sensitive adhesive layer, 7-base paper release film, 8-protective film, 9-polyurea layer, 10-scratch-resistant coating, 11-PET substrate 2, 12-composite adhesive layer. DETAILED DESCRIPTION

[0081] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0082] In the following specific embodiments,

[0083] Carbon nanotubes: CAS number 308068-56-6, purity 99%, from Shandong Tanfeng New Materials Technology Co., Ltd.

[0084] PET: Brand FR530NC010, from Ningbo Oushuo New Materials Co., Ltd.

[0085] Bulletproof glass fiber: brand name EXL4419, sourced from Dongguan Juona New Materials Co., Ltd.

[0086] The nano-ceramic particles are zirconium oxide nanoparticles, CAS number 1314-23-4, purity 99%, particle size 5 μm, from Merck Life Sciences;

[0087] The ultraviolet absorber is UV-531, with a purity of 99%, which comes from Jinan Xiangfeng Weiye Chemical Co., Ltd.

[0088] The base paper release film is a PET silicone oil release film with a thickness of 40-60μm, which comes from Jiangsu Pingyu New Materials Co., Ltd.

[0089] Polyacrylate: CAS number is 9003-01-4, purity is 99%, sourced from Jinan Huijinchuan Trading Co., Ltd.

[0090] Ethyl acetate: CAS number is 141-78-6, purity is 99%, from Foshan Changxing New Materials Co., Ltd.

[0091] The defoamer was BASF FoamStar SI 2299, 99% pure, sourced from DKSH Chemical International Trading (Shanghai) Co., Ltd.;

[0092] The leveling agent is GS-1873, with a viscosity of 150-400cst, from Shanghai Zicheng International Trade Co., Ltd.

[0093] p-Phenylene diisocyanate: CAS number is 104-49-4, purity is 98%, derived from McLean reagent;

[0094] Toluene: CAS number is 108-88-3, from Merck reagent;

[0095] Butanone: CAS number is 78-93-3, purity is 99.8%, sourced from Guangdong Xiaoda Chemical Co., Ltd.;

[0096] Diphenylmethane diisocyanate: CAS number is 101-68-8, from Merck reagents;

[0097] Polycaprolactone polyol: CAS number is 69089-45-8, from Hubei Watson Chemical Technology Co., Ltd.;

[0098] Polytetramethylene ether glycol p-aminobenzoate: CAS number is 54667-43-5, purity is 99%, from Wuhan Kanos Technology Co., Ltd.

[0099] Diethyltoluenediamine: CAS number is 68479-98-1, purity is 99.5%, sourced from Jinan Shengda Chemical Co., Ltd.

[0100] Dichlorodiphenylmethanediamine: CAS number is 101-14-4, purity is 99%, from Jiangsu Bost Chemical Technology Co., Ltd.;

[0101] Toluene: CAS number is 108-88-3, from Merck reagent;

[0102] Butanone: CAS number is 78-93-3, purity is 99.8%, sourced from Guangdong Xiaoda Chemical Co., Ltd.;

[0103] Diphenylmethane diisocyanate: CAS number is 101-68-8, from Merck reagents;

[0104] Polycaprolactone polyol: CAS number is 69089-45-8, from Hubei Watson Chemical Technology Co., Ltd.;

[0105] Polytetramethylene ether glycol p-aminobenzoate: CAS number is 54667-43-5, purity is 99%, from Wuhan Kanos Technology Co., Ltd.

[0106] Diethyltoluenediamine: CAS number is 68479-98-1, purity is 99.5%, sourced from Jinan Shengda Chemical Co., Ltd.

[0107] Dichlorodiphenylmethanediamine: CAS number is 101-14-4, purity is 99%, from Jiangsu Bost Chemical Technology Co., Ltd.;

[0108] Water-based acrylic resin: CAS number is 9003-01-4, viscosity is 100-3000cP, from Guangzhou Haoyi New Materials Technology Co., Ltd.;

[0109] The photoinitiator is ethyl p-N,N-dimethylaminobenzoate, CAS No. 10287-53-3, purity 99%, from Jiangsu Rayne Environmental Protection Technology Co., Ltd.;

[0110] The thickener is sodium polyacrylate, CAS No. 9003-04-7, purity 99%, from Henan Mingzhixin Chemical Products Co., Ltd.

[0111] Polyether diol: hydroxyl value 510-623mgKOH / g, purity 99%, sourced from Hai'an Petrochemical Plant, Jiangsu Province;

[0112] 1,3-Propanediol: CAS number is 504-63-2, purity is 99%, from Nanjing Oriental Pearl Industry and Trade Co., Ltd.;

[0113] The blue dye is acid blue 9, CAS number 3486-30-4, pH value 8.5-9.5;

[0114] The red dye is solvent red 135, CAS number 20749-68-2, purity 99%;

[0115] The black dye is solvent black 29, CAS number 61901-87-9, purity 99%, all from Anhui Jingzhicai New Materials Co., Ltd.;

[0116] The protective film is a PET protective film with a thickness of 40-55 μm, which comes from Wuxi Boli Protective Film Co., Ltd.

[0117] Embodiment 1: A method for preparing a multilayer explosion-proof nanofilm, comprising the following steps:

[0118] (1) Preparation of pressure-sensitive adhesive coating liquid: 30 parts of polyacrylate, 50 parts of ethyl acetate, 0.1 parts of defoamer and 0.1 parts of leveling agent were mixed and stirred for 3 minutes, and dispersed at high speed to obtain a mixed solution 1; 3 parts of p-phenylene diisocyanate and 5 parts of ethyl acetate were mixed and stirred for 5 minutes, and the mixed solution 1 was added and stirred for 10 minutes to obtain a pressure-sensitive adhesive coating liquid; the process conditions for high-speed dispersion were: temperature 20°C, rotation speed 2000 r / min, time 5 minutes;

[0119] (2) Preparation of polyurea coating liquid: 50 parts of ethyl acetate, 5 parts of toluene, 5 parts of butanone, 5 parts of diphenylmethane diisocyanate, 10 parts of polycaprolactone polyol, and 10 parts of polytetramethylene ether glycol p-aminobenzoate were mixed and stirred, 3 parts of diethyltoluenediamine and 3 parts of dichlorodiphenylmethanediamine were added, stirring was continued, 1 part of carbon nanotubes was added, and ultrasonic dispersion was performed to obtain a polyurea coating liquid; the stirring process conditions were: temperature 20°C, rotation speed 500r / min, time 10min; the ultrasonic dispersion process conditions were: frequency 20kHz, time 5min;

[0120] (3) Preparation of composite adhesive coating liquid: 35 parts of toluene, 10 parts of polyether diol, 1 part of 1,3-propylene glycol, 0.1 parts of defoaming agent, 0.1 parts of leveling agent, 1 part of blue dye, 1.5 parts of red dye, and 2.5 parts of black dye were mixed, stirred at 300 r / min for 10 min at 20° C., 45 parts of p-phenylene diisocyanate were added, and stirred at 300 r / min for 5 min at 20° C. to obtain a composite adhesive coating liquid;

[0121] (4) Preparation of a scratch-resistant coating liquid: 30 parts of an aqueous acrylic resin, 10 parts of deionized water, 0.1 parts of a defoamer, 0.1 parts of a leveling agent, and 1 part of a photoinitiator were mixed, and stirred at 550 r / min for 0.3 h at 20° C., and 65 parts of an aqueous acrylic resin and 0.5 parts of a thickener were added again, and the mixture was stirred to adjust the viscosity to 900 CPS to obtain a scratch-resistant coating liquid;

[0122] (5) Preparation of PET substrate 1: PET is blended with carbon nanotubes and bulletproof glass fibers respectively, and placed in a three-layer extruder for extrusion, pulling, and molding to form a three-layer structure of PET containing bulletproof glass fibers-PET containing carbon nanotubes-PET containing bulletproof glass fibers, that is, PET substrate 1 is obtained; the mass ratio of carbon nanotubes to PET is 1:1000; the mass ratio of bulletproof glass fibers to PET is 1:1000; the melting temperature is 200°C, and the cooling temperature is 10°C; the thickness of PET substrate 1 is 120 μm;

[0123] (6) Preparation of PET substrate 2: PET is blended with nano-ceramic particles and ultraviolet absorber respectively, and placed in a three-layer extruder for extrusion, pulling, and molding to form a double-layer structure of PET containing ultraviolet absorber and PET containing nano-ceramic particles, thereby obtaining PET substrate 2; the mass ratio of nano-ceramic particles to PET is 1:1000; the mass ratio of ultraviolet absorber to PET is 1:1000; the melting temperature is 200°C, and the cooling temperature is 10°C; the thickness of PET substrate 2 is 120 μm;

[0124] (7) Preparation of semi-finished product 1: coating one side of PET substrate 1 with pressure-sensitive adhesive coating liquid, drying, and laminating with base paper release film to form a three-layer structure of PET substrate 1-pressure-sensitive adhesive layer-base paper release film, thereby obtaining semi-finished product 1; the pressure-sensitive adhesive coating thickness is 28 μm; and the drying process conditions are: temperature 80° C., time 5 min;

[0125] (8) Preparation of semi-finished product 2: Coat the other side of PET substrate 1 with polyurea coating liquid, dry it, and laminate it with protective film to form a five-layer structure of protective film-polyurea layer-PET substrate 1-pressure-sensitive adhesive layer-bottom paper release film to obtain semi-finished product 2; the drying process conditions are: temperature 80° C., time 5 min; polyurea coating thickness 5 μm;

[0126] (9) Preparation of semi-finished product 3: coating a scratch-resistant coating liquid on one side of the PET substrate 2 containing a UV absorber, drying, and laminating with a protective film to form a three-layer structure of protective film-scratch-resistant coating-PET substrate 2, thereby obtaining a semi-finished product 3; the scratch-resistant coating thickness is 7 μm; the drying process conditions are: temperature 80° C., time 5 min; the protective film thickness is 40 μm;

[0127] (10) Preparation of multi-layer explosion-proof nanofilm: a composite adhesive coating liquid is coated on one side of a semi-finished product 3 containing nano-ceramic particles, dried, and laminated with the semi-finished product 2 with the protective film removed to form an eight-layer structure of protective film-scratch-resistant coating-PET substrate 2-composite adhesive layer-polyurea layer-PET substrate 1-pressure-sensitive adhesive layer-base paper release film to obtain a multi-layer explosion-proof nanofilm; the composite adhesive coating thickness is 10 μm; the drying process conditions are: temperature 80°C, time 5 min.

[0128] Embodiment 2: A method for preparing a multilayer explosion-proof nanofilm, comprising the following steps:

[0129] (1) Preparation of pressure-sensitive adhesive coating liquid: 32 parts of polyacrylate, 52 parts of ethyl acetate, 0.1 parts of defoamer and 0.1 parts of leveling agent were mixed and stirred for 3 minutes, and dispersed at high speed to obtain a mixed solution 1; 3 parts of p-phenylene diisocyanate and 5 parts of ethyl acetate were mixed and stirred for 5 minutes, and the mixed solution 1 was added and stirred for 10 minutes to obtain a pressure-sensitive adhesive coating liquid; the process conditions for high-speed dispersion were: temperature 22° C., rotation speed 2500 r / min, and time 15 minutes;

[0130] (2) Preparation of polyurea coating liquid: 52 parts of ethyl acetate, 6 parts of toluene, 6 parts of butanone, 6 parts of diphenylmethane diisocyanate, 12 parts of polycaprolactone polyol, and 12 parts of polytetramethylene ether glycol p-aminobenzoate were mixed and stirred, 3 parts of diethyltoluenediamine and 3 parts of dichlorodiphenylmethanediamine were added, stirring was continued, 2 parts of carbon nanotubes were added, and ultrasonic dispersion was performed to obtain a polyurea coating liquid; the stirring process conditions were: temperature 22°C, rotation speed 520r / min, time 10min; the ultrasonic dispersion process conditions were: frequency 22kHz, time 6min;

[0131] (3) Preparation of composite adhesive coating liquid: 35 parts of toluene, 10 parts of polyether diol, 1 part of 1,3-propylene glycol, 0.1 parts of defoaming agent, 0.1 parts of leveling agent, 1 part of blue dye, 1.5 parts of red dye, and 2.5 parts of black dye were mixed, stirred at 330 r / min at 22° C. for 12 min, 45 parts of p-phenylene diisocyanate were added, and stirred at 330 r / min at 22° C. for 5 min to obtain a composite adhesive coating liquid;

[0132] (4) Preparation of a scratch-resistant coating liquid: 32 parts of an aqueous acrylic resin, 12 parts of deionized water, 0.2 parts of a defoamer, 0.2 parts of a leveling agent, and 2 parts of a photoinitiator were mixed, and stirred at 550 r / min for 0.3 h at 22° C., and 65 parts of an aqueous acrylic resin and 0.5 parts of a thickener were added again, and the mixture was stirred to adjust the viscosity to 900 CPS to obtain a scratch-resistant coating liquid;

[0133] (5) Preparation of PET substrate 1: PET is blended with carbon nanotubes and bulletproof glass fibers respectively, and placed in a three-layer extruder for extrusion, pulling, and molding to form a three-layer structure of PET containing bulletproof glass fibers-PET containing carbon nanotubes-PET containing bulletproof glass fibers, that is, PET substrate 1 is obtained; the mass ratio of carbon nanotubes to PET is 3:1000; the mass ratio of bulletproof glass fibers to PET is 3:1000; the melting temperature is 200° C., and the cooling temperature is 12° C.; the thickness of PET substrate 1 is 120 μm;

[0134] (6) Preparation of PET substrate 2: PET is blended with nano-ceramic particles and ultraviolet absorber respectively, placed in a three-layer extruder for extrusion, pulling, and molding to form a double-layer structure of PET containing ultraviolet absorber-PET containing nano-ceramic particles, thereby obtaining PET substrate 2; the mass ratio of nano-ceramic particles to PET is 2:1000; the mass ratio of ultraviolet absorber to PET is 2:1000; the melting temperature is 200°C, the cooling temperature is 12°C; the thickness of PET substrate 2 is 120 μm;

[0135] (7) Preparation of semi-finished product 1: coating one side of PET substrate 1 with pressure-sensitive adhesive coating liquid, drying, and laminating with base paper release film to form a three-layer structure of PET substrate 1-pressure-sensitive adhesive layer-base paper release film, thereby obtaining semi-finished product 1; the pressure-sensitive adhesive coating thickness is 28 μm; the drying process conditions are: temperature 90° C., time 5 min;

[0136] (8) Preparation of semi-finished product 2: Coat the other side of PET substrate 1 with polyurea coating liquid, dry it, and laminate it with protective film to form a five-layer structure of protective film-polyurea layer-PET substrate 1-pressure-sensitive adhesive layer-bottom paper release film to obtain semi-finished product 2; the drying process conditions are: temperature 90° C., time 5 min; polyurea coating thickness 8 μm;

[0137] (9) Preparation of semi-finished product 3: coating a scratch-resistant coating liquid on one side of the PET substrate 2 containing a UV absorber, drying, and laminating with a protective film to form a three-layer structure of protective film-scratch-resistant coating-PET substrate 2, thereby obtaining a semi-finished product 3; the scratch-resistant coating thickness is 7 μm; the drying process conditions are: temperature 90° C., time 5 min; the protective film thickness is 45 μm;

[0138] (10) Preparation of multi-layer explosion-proof nanofilm: a composite adhesive coating liquid is coated on one side of a semi-finished product 3 containing nano-ceramic particles, dried, and laminated with the semi-finished product 2 with the protective film removed to form an eight-layer structure of protective film-scratch-resistant coating-PET substrate 2-composite adhesive layer-polyurea layer-PET substrate 1-pressure-sensitive adhesive layer-base paper release film to obtain a multi-layer explosion-proof nanofilm; the composite adhesive coating thickness is 15 μm; the drying process conditions are: temperature 90°C, time 5 min.

[0139] Embodiment 3: A method for preparing a multilayer explosion-proof nanofilm, comprising the following steps:

[0140] (1) Preparation of pressure-sensitive adhesive coating liquid: 35 parts of polyacrylate, 55 parts of ethyl acetate, 0.2 parts of defoamer and 0.2 parts of leveling agent were mixed and stirred for 4 minutes, and dispersed at high speed to obtain a mixed solution 1; 4 parts of p-phenylene diisocyanate and 4 parts of ethyl acetate were mixed and stirred for 5 minutes, and the mixed solution 1 was added and stirred for 13 minutes to obtain a pressure-sensitive adhesive coating liquid; the process conditions for high-speed dispersion were: temperature 25° C., rotation speed 3000 r / min, and time 20 minutes;

[0141] (2) Preparation of polyurea coating liquid: 55 parts of ethyl acetate, 7 parts of toluene, 7 parts of butanone, 7 parts of diphenylmethane diisocyanate, 15 parts of polycaprolactone polyol, and 15 parts of polytetramethylene ether glycol p-aminobenzoate were mixed and stirred, 4 parts of diethyltoluenediamine and 4 parts of dichlorodiphenylmethanediamine were added, stirring was continued, 3 parts of carbon nanotubes were added, and ultrasonic dispersion was performed to obtain a polyurea coating liquid; the stirring process conditions were: temperature 25°C, rotation speed 550r / min, time 13min; the ultrasonic dispersion process conditions were: frequency 25kHz, time 7min;

[0142] (3) Preparation of composite adhesive coating liquid: 37 parts of toluene, 13 parts of polyether diol, 3 parts of 1,3-propylene glycol, 0.3 parts of defoaming agent, 0.3 parts of leveling agent, 1.3 parts of blue dye, 1.7 parts of red dye, and 2.7 parts of black dye were mixed, stirred at 400 r / min for 15 min at 25° C., 47 parts of p-phenylene diisocyanate were added, and stirred at 400 r / min for 7 min at 25° C. to obtain a composite adhesive coating liquid;

[0143] (4) Preparation of a scratch-resistant coating liquid: 33 parts of an aqueous acrylic resin, 13 parts of deionized water, 0.3 parts of a defoamer, 0.3 parts of a leveling agent, and 3 parts of a photoinitiator were mixed, and stirred at 25° C. and 600 r / min for 0.4 h, and 67 parts of an aqueous acrylic resin and 0.7 parts of a thickener were added again, and the mixture was stirred and adjusted to a viscosity of 1000 CPS to obtain a scratch-resistant coating liquid;

[0144] (5) Preparation of PET substrate 1: PET is blended with carbon nanotubes and bulletproof glass fibers respectively, and the mixture is extruded, pulled, and molded in a three-layer extruder to form a three-layer structure of PET containing bulletproof glass fibers-PET containing carbon nanotubes-PET containing bulletproof glass fibers, thereby obtaining PET substrate 1; the mass ratio of carbon nanotubes to PET is 5:1000; the mass ratio of bulletproof glass fibers to PET is 5:1000; the melting temperature is 210° C., and the cooling temperature is 15° C.; the thickness of PET substrate 1 is 160 μm;

[0145] (6) Preparation of PET substrate 2: PET was mixed with nano-ceramic particles and ultraviolet absorber respectively, and extruded, pulled and molded in a three-layer extruder to form a double-layer structure of PET containing ultraviolet absorber and PET containing nano-ceramic particles, thereby obtaining PET substrate 2; the mass ratio of nano-ceramic particles to PET was 3:1000; the mass ratio of ultraviolet absorber to PET was 3:1000; the melting temperature was 210°C, and the cooling temperature was 15°C; the thickness of PET substrate 2 was 160 μm;

[0146] (7) Preparation of semi-finished product 1: coating one side of PET substrate 1 with pressure-sensitive adhesive coating liquid, drying, and laminating with base paper release film to form a three-layer structure of PET substrate 1-pressure-sensitive adhesive layer-base paper release film, thereby obtaining semi-finished product 1; the pressure-sensitive adhesive coating thickness is 28-30 μm; the drying process conditions are: temperature 100° C., time 7 min;

[0147] (8) Preparation of semi-finished product 2: Coating the polyurea coating liquid on the other side of the PET substrate 1, drying, and laminating with the protective film to form a five-layer structure of protective film-polyurea layer-PET substrate 1-pressure-sensitive adhesive layer-bottom paper release film to obtain semi-finished product 2; the drying process conditions are: temperature 100° C., time 7 min; polyurea coating thickness 10 μm;

[0148] (9) Preparation of semi-finished product 3: coating a scratch-resistant coating liquid on one side of the PET substrate 2 containing a UV absorber, drying, and laminating with a protective film to form a three-layer structure of protective film-scratch-resistant coating-PET substrate 2, thereby obtaining a semi-finished product 3; the scratch-resistant coating thickness is 8 μm; the drying process conditions are: temperature 100° C., time 7 min; the protective film thickness is 50 μm;

[0149] (10) Preparation of multi-layer explosion-proof nanofilm: A composite adhesive coating liquid is coated on one side of the semi-finished product 3 containing nano-ceramic particles, dried, and laminated with the semi-finished product 2 with the protective film removed to form an eight-layer structure of protective film-scratch-resistant coating-PET substrate 2-composite adhesive layer-polyurea layer-PET substrate 1-pressure-sensitive adhesive layer-base paper release film to obtain a multi-layer explosion-proof nanofilm; the composite adhesive coating thickness is 20 μm; the drying process conditions are: temperature 100°C, time 7 min.

[0150] Embodiment 4: A method for preparing a multilayer explosion-proof nanofilm, comprising the following steps:

[0151] (1) Preparation of pressure-sensitive adhesive coating liquid: 40 parts of polyacrylate, 60 parts of ethyl acetate, 0.3 parts of defoamer and 0.3 parts of leveling agent were mixed and stirred for 5 minutes, and dispersed at high speed to obtain a mixed solution 1; 5 parts of p-phenylene diisocyanate and 7 parts of ethyl acetate were mixed and stirred for 5 minutes, and the mixed solution 1 was added and stirred for 15 minutes to obtain a pressure-sensitive adhesive coating liquid; the process conditions for high-speed dispersion were: temperature 28° C., rotation speed 4500 r / min, and time 25 minutes;

[0152] (2) Preparation of polyurea coating liquid: 60 parts of ethyl acetate, 10 parts of toluene, 10 parts of butanone, 8 parts of diphenylmethane diisocyanate, 20 parts of polycaprolactone polyol, and 20 parts of polytetramethylene ether glycol p-aminobenzoate were mixed and stirred, 5 parts of diethyltoluenediamine and 5 parts of dichlorodiphenylmethanediamine were added, stirring was continued, 4 parts of carbon nanotubes were added, and ultrasonic dispersion was performed to obtain a polyurea coating liquid; the stirring process conditions were: temperature 30°C, rotation speed 550r / min, time 14min; the ultrasonic dispersion process conditions were: frequency 26kHz, time 9min;

[0153] (3) Preparation of composite adhesive coating liquid: 40 parts of toluene, 15 parts of polyether diol, 5 parts of 1,3-propylene glycol, 0.5 parts of defoaming agent, 0.5 parts of leveling agent, 1.5 parts of blue dye, 2 parts of red dye, and 3 parts of black dye were mixed, stirred at 450 r / min for 17 min at 27° C., 50 parts of p-phenylene diisocyanate were added, and stirred at 450 r / min for 7 min at 27° C. to obtain a composite adhesive coating liquid;

[0154] (4) Preparation of a scratch-resistant coating liquid: 35 parts of an aqueous acrylic resin, 15 parts of deionized water, 0.5 parts of a defoamer, 0.5 parts of a leveling agent, and 5 parts of a photoinitiator were mixed, and stirred at 27° C. and 600 r / min for 0.5 h. 70 parts of an aqueous acrylic resin and 1 part of a thickener were added again, and the mixture was stirred and adjusted to a viscosity of 1000 CPS to obtain a scratch-resistant coating liquid;

[0155] (5) Preparation of PET substrate 1: PET is blended with carbon nanotubes and bulletproof glass fibers respectively, and the mixture is placed in a three-layer extruder for extrusion, pulling, and molding to form a three-layer structure of PET containing bulletproof glass fibers-PET containing carbon nanotubes-PET containing bulletproof glass fibers, thereby obtaining PET substrate 1; the mass ratio of carbon nanotubes to PET is 7:1000; the mass ratio of bulletproof glass fibers to PET is 7:1000; the melting temperature is 220° C., and the cooling temperature is 20° C.; the thickness of PET substrate 1 is 200 μm;

[0156] (6) Preparation of PET substrate 2: PET is blended with nano-ceramic particles and ultraviolet absorber respectively, placed in a three-layer extruder for extrusion, pulling, and molding to form a double-layer structure of PET containing ultraviolet absorber and PET containing nano-ceramic particles, thereby obtaining PET substrate 2; the mass ratio of nano-ceramic particles to PET is 4:1000; the mass ratio of ultraviolet absorber to PET is 4:1000; the melting temperature is 220°C, the cooling temperature is 20°C; the thickness of PET substrate 2 is 200 μm;

[0157] (7) Preparation of semi-finished product 1: coating one side of PET substrate 1 with pressure-sensitive adhesive coating liquid, drying, and laminating with base paper release film to form a three-layer structure of PET substrate 1-pressure-sensitive adhesive layer-base paper release film, thereby obtaining semi-finished product 1; the pressure-sensitive adhesive coating thickness is 30 μm; the drying process conditions are: temperature 120° C., time 10 min;

[0158] (8) Preparation of semi-finished product 2: Coat the other side of PET substrate 1 with polyurea coating liquid, dry it, and laminate it with protective film to form a five-layer structure of protective film-polyurea layer-PET substrate 1-pressure-sensitive adhesive layer-bottom paper release film to obtain semi-finished product 2; the drying process conditions are: temperature 120° C., time 10 min; polyurea coating thickness 12 μm;

[0159] (9) Preparation of semi-finished product 3: coating a scratch-resistant coating liquid on one side of the PET substrate 2 containing a UV absorber, drying, and laminating with a protective film to form a three-layer structure of protective film-scratch-resistant coating-PET substrate 2, thereby obtaining a semi-finished product 3; the scratch-resistant coating thickness is 9 μm; the drying process conditions are: temperature 120° C., time 10 min; the protective film thickness is 50 μm;

[0160] (10) Preparation of multi-layer explosion-proof nanofilm: a composite adhesive coating liquid is coated on one side of a semi-finished product 3 containing nano-ceramic particles, dried, and laminated with the semi-finished product 2 with the protective film removed to form an eight-layer structure of protective film-scratch-resistant coating-PET substrate 2-composite adhesive layer-polyurea layer-PET substrate 1-pressure-sensitive adhesive layer-base paper release film to obtain a multi-layer explosion-proof nanofilm; the composite adhesive coating thickness is 25 μm; the drying process conditions are: temperature 120°C, time 10 min.

[0161] Embodiment 5: A method for preparing a multilayer explosion-proof nanofilm, comprising the following steps:

[0162] (1) Preparation of pressure-sensitive adhesive coating liquid: 40 parts of polyacrylate, 60 parts of ethyl acetate, 0.3 parts of defoamer and 0.3 parts of leveling agent were mixed and stirred for 5 minutes, and dispersed at high speed to obtain a mixed solution 1; 5 parts of p-phenylene diisocyanate and 7 parts of ethyl acetate were mixed and stirred for 5 minutes, and the mixed solution 1 was added and stirred for 15 minutes to obtain a pressure-sensitive adhesive coating liquid; the process conditions for high-speed dispersion were: temperature 30° C., rotation speed 5000 r / min, and time 30 minutes;

[0163] (2) Preparation of polyurea coating liquid: 60 parts of ethyl acetate, 10 parts of toluene, 10 parts of butanone, 8 parts of diphenylmethane diisocyanate, 20 parts of polycaprolactone polyol, and 20 parts of polytetramethylene ether glycol p-aminobenzoate were mixed and stirred, 5 parts of diethyltoluenediamine and 5 parts of dichlorodiphenylmethanediamine were added, stirring was continued, 5 parts of carbon nanotubes were added, and ultrasonic dispersion was performed to obtain a polyurea coating liquid; the stirring process conditions were: temperature 30°C, rotation speed 600r / min, time 15min; the ultrasonic dispersion process conditions were: frequency 28kHz, time 10min;

[0164] (3) Preparation of composite adhesive coating liquid: 40 parts of toluene, 15 parts of polyether diol, 5 parts of 1,3-propylene glycol, 0.5 parts of defoaming agent, 0.5 parts of leveling agent, 1.5 parts of blue dye, 2 parts of red dye, and 3 parts of black dye were mixed, stirred at 500 r / min at 30° C. for 20 min, 45-50 parts of p-phenylene diisocyanate were added, and stirred at 500 r / min at 30° C. for 10 min to obtain a composite adhesive coating liquid;

[0165] (4) Preparation of a scratch-resistant coating liquid: 35 parts of an aqueous acrylic resin, 15 parts of deionized water, 0.5 parts of a defoamer, 0.5 parts of a leveling agent, and 5 parts of a photoinitiator were mixed, and stirred at 650 r / min for 0.5 h at 30° C., and 70 parts of an aqueous acrylic resin and 1 part of a thickener were added again, and the mixture was stirred to adjust the viscosity to 1100 CPS to obtain a scratch-resistant coating liquid;

[0166] (5) Preparation of PET substrate 1: PET is blended with carbon nanotubes and bulletproof glass fibers respectively, and placed in a three-layer extruder for extrusion, pulling, and molding to form a three-layer structure of PET containing bulletproof glass fibers-PET containing carbon nanotubes-PET containing bulletproof glass fibers, that is, PET substrate 1 is obtained; the mass ratio of carbon nanotubes to PET is 10:1000; the mass ratio of bulletproof glass fibers to PET is 10:1000; the melting temperature is 220°C, and the cooling temperature is 20°C; the thickness of PET substrate 1 is 200 μm;

[0167] (6) Preparation of PET substrate 2: PET is mixed with nano-ceramic particles and ultraviolet absorber respectively, and placed in a three-layer extruder for extrusion, pulling, and molding to form a double-layer structure of PET containing ultraviolet absorber and PET containing nano-ceramic particles, thereby obtaining PET substrate 2; the mass ratio of nano-ceramic particles to PET is 5:1000; the mass ratio of ultraviolet absorber to PET is 5:1000; the melting temperature is 220°C, and the cooling temperature is 20°C; the thickness of PET substrate 2 is 200 μm;

[0168] (7) Preparation of semi-finished product 1: coating one side of PET substrate 1 with pressure-sensitive adhesive coating liquid, drying, and laminating with base paper release film to form a three-layer structure of PET substrate 1-pressure-sensitive adhesive layer-base paper release film, thereby obtaining semi-finished product 1; the pressure-sensitive adhesive coating thickness is 30 μm; the drying process conditions are: temperature 120° C., time 10 min;

[0169] (8) Preparation of semi-finished product 2: Coating the polyurea coating liquid on the other side of the PET substrate 1, drying, and laminating with the protective film to form a five-layer structure of protective film-polyurea layer-PET substrate 1-pressure-sensitive adhesive layer-bottom paper release film to obtain semi-finished product 2; the drying process conditions are: temperature 120° C., time 10 min; polyurea coating thickness 15 μm;

[0170] (9) Preparation of semi-finished product 3: coating a scratch-resistant coating liquid on one side of the PET substrate 2 containing a UV absorber, drying, and laminating with a protective film to form a three-layer structure of protective film-scratch-resistant coating-PET substrate 2, thereby obtaining a semi-finished product 3; the scratch-resistant coating thickness is 9 μm; the drying process conditions are: temperature 120° C., time 10 min; the protective film thickness is 55 μm;

[0171] (10) Preparation of multi-layer explosion-proof nanofilm: a composite adhesive coating liquid is coated on one side of a semi-finished product 3 containing nano-ceramic particles, dried, and laminated with the semi-finished product 2 with the protective film removed to form an eight-layer structure of protective film-scratch-resistant coating-PET substrate 2-composite adhesive layer-polyurea layer-PET substrate 1-pressure-sensitive adhesive layer-base paper release film to obtain a multi-layer explosion-proof nanofilm; the composite adhesive coating thickness is 30 μm; the drying process conditions are: temperature 120°C, time 10 min.

[0172] Comparative Example 1: Compared with Example 1, carbon nanotubes were not added during the preparation of the polyurea coating liquid, and other conditions remained unchanged.

[0173] Experiment: The multilayer explosion-proof nanofilms obtained in Examples 1-5 and Comparative Example 1 were prepared into samples and their performance was tested;

[0174] Transmittance and haze test: Use a transmittance-haze meter with a wavelength of 500nm to test the sample;

[0175] Infrared and ultraviolet blocking rate: Make the sample into 10cm×10cm size and place it on an optical detector to test the ultraviolet and infrared transmittance;

[0176] Impact resistance: The multilayer explosion-proof nanofilm obtained in Examples 1-5 and Comparative Example 1 was placed on a bracket, and a steel ball weighing 1040 g was freely dropped from a height of 4 m from the nanofilm to impact the center of the nanofilm; the state of the nanofilm was observed;

[0177] Light transmittance / % Haze / % Infrared blocking rate / % UV blocking rate / % state Example 1 75 0.6 98 100 Shatter Example 2 74 0.7 99 100 Shatter Example 3 72 0.8 99 100 Unbroken Example 4 68 1.2 99 100 Unbroken Example 5 65 1.6 99 100 Shatter Comparative Example 1 78 0.6 96 100 Shatter

[0178] Table 1 Performance test of multi-layer explosion-proof nanofilm

[0179] According to the data in the above table, different amounts of carbon nanotubes are added in Examples 1-5, which have better infrared blocking rates than Comparative Example 1, and when 3-4 parts of carbon nanotubes are added, the impact strength is the best. The light transmittance of Comparative Example 1 is better and the haze is lower, but the infrared blocking rate and impact strength are poor; however, too much carbon nanotubes are added in Example 5, which also leads to a decrease in its impact strength. It can be seen that the multi-layer explosion-proof film prepared by the present invention not only maintains the anti-ultraviolet and heat insulation functions of conventional explosion-proof films, but also has good explosion-proof and anti-puncture functions, and has a certain degree of safety.

[0180] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for making a multi-layer explosion-proof nanofilm, characterized in that: The following steps are involved: Step (1): PET is blended with carbon nanotubes and bulletproof glass fibers respectively, and the mixture is placed in a three-layer extruder for extrusion, pulling, and molding to form a three-layer structure of PET containing bulletproof glass fibers-PET containing carbon nanotubes-PET containing bulletproof glass fibers, thereby obtaining a PET substrate 1; Step (2): PET is blended with nano-ceramic particles and ultraviolet absorber respectively, and the mixture is placed in a three-layer extruder for extrusion, pulling, and molding to form a double-layer structure of PET containing ultraviolet absorber and PET containing nano-ceramic particles, thereby obtaining a PET substrate 2; Step (3): coating one side of the PET substrate 1 with a pressure-sensitive adhesive coating liquid, drying, and laminating with a base paper release film to form a three-layer structure of PET substrate 1-pressure-sensitive adhesive layer-base paper release film, thereby obtaining a semi-finished product 1; Step (4): coating the other side of the PET substrate 1 with a polyurea coating liquid, drying, and laminating with a protective film to form a five-layer structure of protective film-polyurea layer-PET substrate 1-pressure-sensitive adhesive layer-base paper release film to obtain a semi-finished product 2; Step (5): coating a scratch-resistant coating liquid on one side of the PET substrate 2 containing a UV absorber, drying, and laminating with a protective film to form a three-layer structure of protective film-scratch-resistant coating-PET substrate 2, thereby obtaining a semi-finished product 3; Step (6): Coat the composite adhesive coating liquid on one side of the semi-finished product 3 containing nano-ceramic particles, dry it, and laminate it with the semi-finished product 2 with the protective film removed to form an eight-layer structure of protective film-scratch-resistant coating-PET substrate 2-composite adhesive layer-polyurea layer-PET substrate 1-pressure-sensitive adhesive layer-base paper release film to obtain a multi-layer explosion-proof nanofilm.

2. The method for making a multi-layer explosion-proof nanofilm according to claim 1, characterized in that: The pressure-sensitive adhesive coating liquid in step (3) is prepared by the following process: The polyacrylate, ethyl acetate, defoamer and leveling agent are mixed and dispersed at high speed, and p-phenylene diisocyanate and ethyl acetate are added and stirred evenly to obtain a pressure-sensitive adhesive coating liquid.

3. The method for making a multi-layer explosion-proof nanofilm according to claim 1, characterized in that: The polyurea coating liquid in step (4) is prepared by the following process: Ethyl acetate, toluene, butanone, diphenylmethane diisocyanate, polycaprolactone polyol and polytetramethylene ether diparaaminobenzoate are mixed and stirred, diethyltoluenediamine and dichlorodiphenylmethanediamine are added, stirring is continued, carbon nanotubes are added, and ultrasonic dispersion is performed to obtain a polyurea layer coating liquid.

4. The method for making a multi-layer explosion-proof nanofilm according to claim 1, characterized in that: The scratch-resistant coating liquid in step (5) is prepared by the following process: The water-based acrylic resin, deionized water, defoamer, leveling agent and photoinitiator are mixed, and after stirring, the water-based acrylic resin and thickener are added again, and the mixture is stirred to adjust the viscosity to 900-1100 CPS to obtain a scratch-resistant coating liquid.

5. The method for making a multi-layer explosion-proof nanofilm according to claim 1, characterized in that: The composite adhesive coating liquid in step (6) is prepared by the following process: Mix toluene, polyether diol, 1,3-propylene glycol, defoamer, leveling agent, blue dye, red dye and black dye, stir evenly, add p-phenylene diisocyanate, continue stirring to obtain a composite adhesive coating liquid.

6. The method for making a multi-layer explosion-proof nanofilm according to claim 2, characterized in that: The mass ratio of polyacrylate, ethyl acetate, defoamer and leveling agent is (30-40): (50-60): (0.1-0.3): (0.1-0.3); the mass ratio of p-phenylene diisocyanate and ethyl acetate is (3-5): (5-7).

7. The method for making a multi-layer explosion-proof nanofilm according to claim 3, characterized in that: The mass ratio of ethyl acetate, toluene, butanone, diphenylmethane diisocyanate, polycaprolactone polyol, polytetramethylene ether diparaaminobenzoate, diethyltoluenediamine, dichlorodiphenylmethanediamine, and carbon nanotubes is (50-60): (5-10): (5-10): (5-8): (10-20): (10-20): (3-5): (3-5): (1-5).

8. The method for making a multi-layer explosion-proof nanofilm according to claim 4, characterized in that: The mass ratio of water-based acrylic resin, deionized water, defoamer, leveling agent, photoinitiator, water-based acrylic resin added again, and thickener is (30-35): (10-15): (0.1-0.5): (0.1-0.5): (1-5): (60-70): (0.5-1).

9. The method for making a multi-layer explosion-proof nano film according to claim 5, characterized in that: The mass ratio of toluene, polyether diol, 1,3-propylene glycol, defoamer, leveling agent, blue dye, red dye, black dye and p-phenylene diisocyanate is (35-40):(10-15):(1-5):(0.1-0.5):(0.1-0.5):(1-1.5):(1.5-2.0):(2.5-3):(40-50).

10. A multi-layer explosion-proof nanofilm, characterized in that: The invention is prepared by the preparation process described in any one of claims 1 to 9.